PENGARUH PEMBERIAN CAMPURAN CAIRAN REBUSAN KAYU SECANG (CAESALPIA SAPPAN L.) DAN DAUN LIDAH BUAYA (ALOE VERA) TERHADAP KADAR GLUKOSA DARAH MENCIT (MUS MUSCULUS) - PUJI LESTARI, NIHAYAH Puji; Tjandrakirana, Tjandrakirana (Universitas Negeri Surabaya, 2013)
The main symptom of diabetes mellitus is an increase of blood glucose concentration, therefore it can be decreased using natural substances. The research aimed to the combination of Caesalpania sappan L wood and Aloe vera leaves liquids can decrease the concentration of blood glucose in Mus musculus. This research used pre-post-test design with RAL. The subjects were 24 Mus musculus of BALB/cAnN strain. The chemical subtance used to increase the concentration of blood glucose was 1 cc/kgBB of dextrose monohydrate 5 %. The animals were devided into 6 groups that are threated by giving: 1) aquades (KK); 2) Caesalpania sappan L wood liquid 100% (KP1); 3) Aloe vera leaves liquid 100% (KP2); 4) combination of Caesalpania sappan L wood and Aloe vera leaves liquid 20% (KP3); 5) combination of Caesalpania sappan L wood and Aloe vera leaves liquid 40% (KP4); 6) combination of Caesalpania sappan L wood and Aloe vera leaves liquid 60% (KP5). The concentration of blood glucose was measured using glico test. The data gained were analyzed using T test and One-Way ANOVA at 5% of level test. After giving dextrose monohydrate the glucose concentration of all samples was 160,75 mg/dl.The results of this research shows that the decrease of glucose concentration of KP1 was 123,75 mg/dl; KP2 was 120,25 mg/dl; KP3 was 118,5 mg/dl; KP4 was 115,75 mg/dl; and KP5 was 109,75 mg/dl. The analysis result revealed that combination of Caesalpania sappan L wood and Aloe vera leaves liquids can decrease of the concentration of blood glucose in Mus musculus (Fcount (3,499) > Ftable (1,83) with sig value < 0,05) and (tcount (10,939) > ttable (1,714)) with sig value < 0,05) . It can be concluded that the combination of Caesalpania sappan L wood and Aloe vera leaves liquids can decrease the concentration of blood glucose in Mus musculus.